2018
DOI: 10.1016/j.ijpharm.2017.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Proliposome tablets manufactured using a slurry-driven lipid-enriched powders: Development, characterization and stability evaluation

Abstract: Proliposome powders were prepared via a slurry method using sorbitol or D-mannitol as carbohydrate carriers in 1:10 or 1:15 w/w lipid phase to carrier ratios. Soya phosphatidylcholine (SPC) and cholesterol were employed as a lipid phase and Beclometasone dipropionate (BDP) was incorporated as a model drug. Direct compaction using a Minipress was applied on the lipid-enriched powder in order to manufacture proliposome tablets. Sorbitol-based proliposome tablets in a 1:15 w/w ratio were found to be the best form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Being structurally similar to biological membranes, unlike polyoxyethylated castor oil, are not associated with hypersensitivity reactions (15,16). Hydrophobic compounds are commonly entrapped within the concentric bilayers of the vesicles, whereas hydrophilic molecules position into the central aqueous core (17). A number of studies have demonstrated that PTX can be entrapped into liposomes bilayers without PEGylation (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being structurally similar to biological membranes, unlike polyoxyethylated castor oil, are not associated with hypersensitivity reactions (15,16). Hydrophobic compounds are commonly entrapped within the concentric bilayers of the vesicles, whereas hydrophilic molecules position into the central aqueous core (17). A number of studies have demonstrated that PTX can be entrapped into liposomes bilayers without PEGylation (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…However, a notable limitation of liposomes however is poor stability upon storage (31)(32)(33) exhibited by aggregation or fusion of vesicles and drug leakage from the vesicles (17,34). The formulation of liposomes in a dry-stable form referred to as proliposomes (which may be hydrated with water to generate liposomes) has been developed as a solution to stability issues associated with the vesicles (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…In 1986, Payne et al [ 24 ] introduced dry and free-flowing liposomal formulations that could produce multi-lamellar liposomes upon hydration. These systems were given the name “proliposomal formulations” and have been a subject of various studies [ 5 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite liposomes enable an antitumor agent to improve solubility and bioavailability, inherent limitation such as aggregation, drug leakage, sedimentation, phospholipid susceptibility to oxidation and hydrolysis still exist 26,27. In order to overcome these issues, a proliposome formulation, dry and free-flowing granular powder, which can disperse to form liposomes suspension via addition of water, is adopted in the current study 28…”
Section: Introductionmentioning
confidence: 99%